STRUCTURAL SYNTHESIS OF PULSE-FREQUENCY FUZZY-LOGIC ELEMENTS - Semenova, Olena; Wojciechowska, Olga (Scientific Works of Vinnytsia National Technical University, 2015)
In this article a method of fuzzy-logic elements structural synthesis has been proposed. The elements are made of basis circuits, which perform operations of addition, subtraction, partition, and division by two. Block diagrams of elements have been synthesized. The elements perform such operations as implication, contradiction, and equivalence. Information in the developed elements is presented as pulse-frequency sig-nals.